IMAGE TOOLS OF USING POEM IN SPONTANEOUS SPEECH - A. Abzhelieva , Diana; S. Dubkova, Julia; R. Nasibullaeva, Elina; V. Petrov, Aleksandr; Yu. Timofeeva , Natalia (Gênero & Direito, 2020)
The article presents a figurative component in spontaneous speech. It is proved that an image enriches speech, and provides its individualization. Imagery testifies to the creative potential of an individual. It represents a deviation from accepted communicative cliches. Experimental word formation is considered as a source of imagery. A significant role is played by the phenomenon of abbreviation semantics in the process of nomination and renomination.